Substrate inhibition during bio-filtration of TCE using diazotrophic bacterial community - Shukla A.K.; Singh R.S.; Upadhyay S.N.; Dubey S.K. (My University, 2025)
The kinetics of biodegradation of TCE in the biofilter packed with wood charcoal and inoculated with diazotrophic bacterial community had been investigated. Use of Michaelis-Menten type model showed that substrate inhibition was present in the system. The kinetic model proposed by Edwards (1970) was used to calculate kinetic parameters-maximum elimination capacity (ECmax), substrate constant (Ks), and inhibition constant (KI). The model fitted well with the experimental data and the ECmax was found to be in the range of 10.8-6.1g/m3h. The Ks values depended upon substrate concentration and ranged from 0.024 to 0.043g/m3 indicating the high affinity of diazotrophs for TCE. The KI values were low and nearly constant (0.011-0.015g/m3) indicating a moderate substrate inhibition. © 2010 Elsevier Ltd.